Population-Based Survival Analysis of Patients With Limb Rhabdomyosarcoma and Metastasis at Diagnosis - Yang, Chunying; Wang, Haiqing; Niu, Feng; Yao, Lufeng (Frontiers in Surgery, 2021)
Purpose: Given the poor prognosis and the relative rarity of limb rhabdomyosarcoma (LRMS) patients with metastasis at diagnosis, we performed this study to reveal distinctive clinical features and evaluate prognostic factors of this special population，in order to provide appropriate treatment. Patients and Methods: We carried out a retrospective research of patients diagnosed as LRMS with metastasis at diagnosis from 1975 to 2016, using the Surveillance, Epidemiology, and End Results (SEER) program database. Survival curves were generated by applying the Kaplan-Meier method. In terms of evaluating and determining the independent predictors of survival, we conducted univariate and multivariate survival analyses, using the Cox proportional hazard regression model. Results: This retrospective analysis contained a series of 245 metastatic LRMS patients with male predominance (male vs female, 1.6:1). Nearly half of the patients were diagnosed with alveolar rhabdomyosarcoma (44.9%). According to results of univariate and multivariate analyses, younger age, tumor subtype and radiotherapy were found to be significantly associated with improved OS and CSS. Conclusions: LRMS patients with metastasis at diagnosis experienced quite poor prognosis. Age at diagnosis, tumor subtype and radiotherapy can help clinicians to better estimate the prognosis. This study indicated local radiotherapy can provide survival benefit.